Metatranscriptomic holobiont analysis of carbohydrate-active enzymes in the millipede Telodeinopus aoutii (Diplopoda, Spirostreptida) - Sardar, Puspendu; Šustr, Vladimír; Chroňáková, Alica; Lorenc, František (Frontiers in Ecology and Evolution, 2022)
As important decomposers of soil organic matter, millipedes contribute to lignocellulose decomposition and nutrient cycling. The degradation of lignocellulose requires the action of several carbohydrate-active enzymes (CAZymes) and, in most invertebrates, depends on the activity of mutualistic gut microorganisms. To address the question of the importance of the microbiota and endogenous (host) enzymes in digestive processes in millipedes, we analyzed metatranscriptomic data from the tropical millipede Telodeinopus aoutii at the holobiont level. Functional annotation included identification of expressed CAZymes (CAZy families and EC terms) in the host and its intestinal microbiota, foregut, midgut, and hindgut, compared to non-intestinal tissues. Most of the 175 CAZy families were expressed exclusively in the gut microbiota and more than 50% of these microbial families were expressed exclusively in the hindgut. The greatest diversity of expressed endogenous CAZymes from all gut sections was found in the midgut (77 families). Bacteria were the major microbial producers of CAZymes, Proteobacteria dominating in the midgut and Bacteriodetes with Firmicutes in the hindgut. The contribution of the eukaryotic microbiota to CAZymes production was negligible. Functional classification of expressed CAZy families confirmed a broad functional spectrum of CAZymes potentially expressed in the holobiont. Degradation of lignocellulose in the digestive tract of the millipede T. aoutii depends largely on bacterial enzymes expressed in the hindgut. Endogenous cellulases were not detected, except for the potentially cellulolytic family AA15, but an expression of cellulolytic enzymes of this family was not confirmed at the EC-number level. The midgut had the greatest diversity of expressed endogenous CAZymes, mainly amylases, indicating the importance of digesting α-glucosidases for the millipede. In contrast, bacterial lignocellulolytic enzymes are sparsely expressed here. The hindgut was the hotspot of microbial degradation of cellulose and hemicellulases. The gain of the millipede from the microbial lignocellulose degradation in the gut, and consequently the mutualistic status of the relationship between the millipede and its cellulolytic gut bacteria, depends on the ability of the millipede to take up microbial metabolites as nutrients through the hindgut wall. Enzymes expressed in the intestine can degrade all components of lignocellulose except lignin. Assuming that soil microbiota is partially degraded lignin in the millipede diet, T. aoutii can be considered a decomposer of soil organic matter relying primarily on its gut bacteria. The deposition of millipede fecal pellets containing an organic matter modified by the hindgut bacterial community could be of ecological significance.